Virulence plasmids of enteroinvasive Escherichia coli and Shigella flexneri integrate into a specific site on the host chromosome: integration greatly reduces expression of plasmid-carried virulence genes. - Zagaglia, C (1991)
The ability of enteroinvasive Escherichia coli and Shigella flexneri to cause disease depends on the presence of a large virulence plasmid (pINV). In this report we show that pHN280, the pINV of the O135:K-:H- enteroivasive strain E. coli HN280, and pWR100, the pINV of S. flexneri serotype 5 strain M90T, are able to integrate into a specific site on the host chromosome. pINV-integrated HN280 and M90T strains required methionine (Met-) to grow in minimal medium, were noninvasive, did not produce contact-mediated hemolysin, and had lost the ability to bind Congo red (Crb-) at 37 degrees C. Immunoblots of whole bacterial extracts from pHN280-integrated HN280 derivatives revealed that integration severely reduced the expression of ipa and virG (icsA) plasmid genes. Met- HN280 and M90T derivative strains spontaneously generated Met+ revertants that either contained excised forms of pINV or had lost pINV. Restriction analysis of excised pINVs showed that they either were virtually identical to parental pINVs (precise excision) or had suffered some deletion (imprecise excision). Precisely excised pINVs expressed the full pattern of virulence, whereas imprecisely excised pINVs were always Crb- and noninvasive. The revertion to Met+ was shown to be recA dependent, indicating that homologous plasmid and chromosomal DNA sequences are involved in the integration-excision process. The maintainance of pINV through integration and downregulation of its virulence genes may represent an advantageous mechanism for enteroinvasive bacteria, particularly when they are outside host cells and/or have to face adverse environmental conditions.